Recognition of deferred income and its influence on the financial economic information of a distributor in the city of Tacna - Pacheco Fernández, Juana Carolina (2020)
This research work analyzes how deferred income influences the financial and economic information of the Distribuidora Malibú SAC in the city of Tacna, period 2014 - 2017. It was observed that, of all sales made, only 27,45 have been delivered % and 72,55% are pending delivery, generating the problem of recognition of deferred income. In financial and economic information, the highest profit was in the period 2015, being S / 21 227,56. The operating margin in the period 2014 had a negative result, while in 2015 it was S / 31 091,72, being S / 687,42 in 2016 and S / 18 896,84 in 2017. The gross margin does not maintain an ascending line due to the difference between declared and accounted income.